The Influence of Culture on Goal Perception: Qatar Versus Denmark. Issue 6 (November 2016) - Ottsen, Christina Lundsgaard; Koppel, Jonathan; Johannessen, Kim Berg; Berntsen, Dorthe
Summary: Expectations of control put forth by societal norms impose a constant influence on goal perception. To examine the influence of culture on perception of personal goals, 124 Middle Easterners and 128 Scandinavians rated their perceived locus of control, generated goals and evaluated goal characteristics. Findings show several cultural and gender differences, most notably in perceived locus of control, unhappiness despite goal achievement and adherence to cultural life script. Many differences were qualified by interactions, suggesting that Middle Eastern men deviate from Middle Eastern women and Scandinavians of both sexes. The Middle Eastern men demonstrated greater ambivalence regarding goal achievement, and contrary to previous findings from other cultural samples, they also showed a significant positive association between internal and external control. Furthermore, goals generated by Middle Easterners showed a greater overlap with their imagined future events, and were largely represented by life script events. These findings are consistent with the view that especially Middle Eastern men experience a greater responsibility for the fulfilment of culturally defined goals. Copyright © 2016 John Wiley & Sons, Ltd.